2021
DOI: 10.1089/end.2020.1210
|View full text |Cite
|
Sign up to set email alerts
|

Greater Renal Function Benefit from Enucleation Technique for More Complex Renal Tumors in Robot-Assisted Partial Nephrectomy

Abstract: Background: Tumor enucleation technique in robot-assisted partial nephrectomy (RAPN) reportedly contributes to renal function preservation. Which tumors and which part to utilize this technique have not been determined. Patients and Methods: This multi-institutional retrospective study included patients who underwent RAPN at tertiary surgery centers. Patients were first stratified into High, Intermediate, and Low categories based on renal nephrometry score. Patients were further classified into I/B-enucleation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…As recently described, enucleation required more WIT than resection, during tumor excision. 26 These data suggest that reserved renal mass volume might be of utmost importance in terms of renal function, although we could not carry out volumetric analysis due to a shortage of information. 6,21,23,26 The present result, that renal function recovery from AKI does not differ between two matched groups, might also be explained by the so-called "synergetic" relationship between ischemic time and surgical precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As recently described, enucleation required more WIT than resection, during tumor excision. 26 These data suggest that reserved renal mass volume might be of utmost importance in terms of renal function, although we could not carry out volumetric analysis due to a shortage of information. 6,21,23,26 The present result, that renal function recovery from AKI does not differ between two matched groups, might also be explained by the so-called "synergetic" relationship between ischemic time and surgical precision.…”
Section: Discussionmentioning
confidence: 99%
“…26 These data suggest that reserved renal mass volume might be of utmost importance in terms of renal function, although we could not carry out volumetric analysis due to a shortage of information. 6,21,23,26 The present result, that renal function recovery from AKI does not differ between two matched groups, might also be explained by the so-called "synergetic" relationship between ischemic time and surgical precision. 7 Furthermore, as the median WIT was 19.0 min and nowhere near the threshold of 30 min in the shorter group, even when matched for RENAL nephrometry score, some other measures to weigh surgical difficulty might be required.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ishiyama et al in 2021 compared the outcomes for 704 patients with T1 renal tumors who underwent RAPN either using the enucleation or standard resection technique. Their data showed that enucleation contributed to early preservation of renal function as measured by eGFR, without compromising oncological margins or patient outcomes (16). Interestingly, trifecta attainment was emphasized in patients with more complex renal tumors, whereby preservation of renal functions when compared to standard resection was most pronounced in the complex tumor group (16).…”
Section: Progression Of Nephron Sparing Surgerymentioning
confidence: 99%